Tax Rate Adjustment and Its Potential Impact on Price: An Application Mathematical Input-Output Price Spillover Model - Hong, Cheng-Yih; Tsai, Yi-Chi; Lee, Tsai- Rong; Dang, Hui-Wen (International Journal of Economics and Financial Issues, 2018)
For a long time the failure of the Transformation of the Industrial Structure and the impact of the financial crisis of 2008, Taiwan promoted tax reform to solve economic development and environmental protection, and the tax rate adjustment of business tax and energy tax became the focus of the tax reform. Empirical evidences suggests that raising business tax by 1% affects the price level, with increases in the corporate goods price index and consumer price index of 1.9474% and 1.37%, respectively, although both remain under 2%. The results of the study found that CGPI and CPI change in energy tax, the sectors affected the most of the chemical industries (4.23%) and service industries (4.04%). Keywords: Tax Rate Adjustment, Price Spillover, Mathematical Input-Output Price Spillover Model JEL Classifications: H2, D57, Q4